Differential mosquito attraction to humans is associated with skin-derived carboxylic acid levels - De Obaldia, Maria Elena; Morita, Takeshi; Dedmon, Laura C; Boehmler, Daniel J; Jiang, Caroline S; Zeledon, Emely V; Cross, Justin R; Vosshall, Leslie B (Cell, 2022)
Some people are more attractive to mosquitoes than others, but the mechanistic basis of this phenomenon is poorly understood. We tested mosquito attraction to human skin odor and identified people who are exceptionally attractive or unattractive to mosquitoes. These differences were stable over several years. Chemical analysis revealed that highly attractive people produce significantly more carboxylic acids in their skin emanations. Mutant mosquitoes lacking the chemosensory co-receptors Ir8a, Ir25a, or Ir76b were severely impaired in attraction to human scent, but retained the ability to differentiate highly and weakly attractive people. The link between elevated carboxylic acids in "mosquito-magnet" human skin odor and phenotypes of genetic mutations in carboxylic acid receptors suggests that such compounds contribute to differential mosquito attraction. Understanding why some humans are more attractive than others provides insights into what skin odorants are most important to the mosquito and could inform the development of more effective repellents.